Prognostic and clinicopathological role of soluble programmed cell death ligand-1 in patients with diffuse large B-cell lymphoma: a meta-analysis - Lu, Hongbin; Luo, Lulu; Mi, Jie; Sun, Min; Wang, Huaping; Wang, Zheng; Ding, Wenwen (Frontiers in Oncology, 2025)
BackgroundThe significance of soluble programmed death protein ligand-1 (PD-L1) in predicting the prognosis of diffuse large B-cell lymphoma (DLBCL) has been previously analyzed, but with conflicting results. This study investigated the effect of soluble PD-L1 (sPD-L1) expression on the prognosis of patients with DLBCL.MethodsWe comprehensively searched the Web of Science, PubMed, Embase, and CNKI databases between their inception and August 14, 2024. The value of sPD-L1 in predicting the overall survival (OS) and progression-free survival (PFS) of patients with DLBCL was analyzed by computing the combined hazard ratios (HRs) and 95% confidence intervals (CIs). Associations between sPD-L1 and the clinicopathological factors of DLBCL were explored by combining odds ratios (ORs) and 95%CIs.ResultsSeven articles involving 826 patients were included in this meta-analysis. Based on our pooled data, elevated sPD-L1 was closely related to poor OS (HR = 2.81, 95%CI = 1.99–3.95, p < 0.001) and inferior PFS (HR = 3.16, 95%CI = 1.41–7.08, p = 0.005) of DLBCL. Moreover, based on the pooled data, higher sPD-L1 was significantly related to the Eastern Cooperative Oncology Group Performance Status Scale (ECOG PS) ≥2 (OR=4.10, 95%CI=1.82-9.24, p=0.001), clinical stage III-IV (OR = 3.30, 95%CI = 1.48–7.39, p = 0.004), elevated lactate dehydrogenase (LDH) levels (OR = 2.14, 95%CI = 1.07–4.30, p = 0.032), and the International Prognostic Index (IPI) score 3–5 (OR = 3.83, 95%CI = 1.91–7.68, p < 0.001) in DLBCL.ConclusionAccording to our findings, a higher sPD-L1 level was a significant predictor of poor OS and PFS in patients with DLBCL. Elevated sPD-L1 levels are closely related to factors representing disease aggressiveness in DLBCL.